Linear free energy relationships in theoretical NMR 13С spectra of sin-[(1-R-η3 -C3H4)Pd(Me2C=O)2]+ complexes - M. H. Elhussien; E. M. Evstigneeva; V. R. Flid (Тонкие химические технологии)
Both theoretical values of NMR 13С chemical shifts and frontier orbital energies (DFT method) for syn-[(1-R-η3-C3H4)Pd(Me2C=O)2]+ follow one- and two-parameter linear regressions which involve σ+ and σ- constants, as well as Swain-Lupton parameters R+, R- and F.